'Digital indigestion': cumbia, class and a post-digital ethos in Buenos Aires. Issue 2 (30th April 2015) - Baker, Geoffrey
Abstract This article focuses on three recent manifestations of cumbia in Buenos Aires, Argentina: digital cumbia released by ZZK Records; retro cumbia orchestras; and a newer strand of digital cumbia, música turra. The first two are identified with the middle class, whereas the third emerged from the clases populares ('popular classes'). Música turra is underpinned by government policies towards digital inclusion, while middle-class incursions into the traditionally working-class sphere of cumbia, too, suggest increasing social cohesion. However, the digital fascination of música turra contrasts with an embrace of the analogue and acoustic in middle-class cumbia. These developments point to the emergence of a post-digital ethos and a shift from a digital to a post-digital divide, also running along class lines, analysed here through a Bourdieusian lens of taste and distinction. While transnational in nature, the post-digital ethos appears in Buenos Aires in a distinctive local form, articulated to growing Latin Americanism and post-neoliberalism on the part of the middle class.